STUDENTS’ PERCEPTION OF EDMODO USE IN ENGLISH CLASS - Ridho Kurniawan; Yahfenel Evi Fussalam; Deka Ismi Mori Saputra (STKIP Muhammadiyah Muara Bungo, 2021)
The use of technology in learning is an effort made in the classroom to increase student participation, motivation and learning outcomes. Edmodo as a technology that can be used in learning has features that facilitate students to learn and play through dynamic games. This article contains the results of research from students' experiences in using Edmodo. Data collection was carried out by distributing questionnaires to students regarding the use of features in Edmodo; the extent to which this affects their learning activities in class and also their motivation to learn. The results of this study indicate that the use of Edmodo affects the dynamics of learning in the classroom, student involvement, learning experiences and student learning motivation. In addition, the use of Edmodo features is also very influential in reducing student focus in learning and improving the quality of learning in comparison. learn in a conventional manner. In addition, another factor that affects the improvement of learning using Edmodo is suitable content which is complemented by feedback to students.